Integration of Religious and Cultural Values in Religious Education: A Collaborative Study Between Indonesia and Malaysia for Student Character Development - Ahmad Sulhan; Hendy Aldian; Nordin Bin Mamat (Electronic Journal of Education, Social Economics and Technology, 2025)
The Study aims to achieve the following objectives: 1. To integrate religious and cultural values into education, which can influence the character development of students in Indonesia and Malaysia; 2. To analyze forms of elaboration on Islamic religious education based on religious and cultural values that can be applied to character development in Indonesia. The research adopts a qualitative approach with a comparative study design. It was conducted in several schools in Indonesia and Malaysia that implement religious education based on religious and cultural values. Primary data were obtained through in-depth interviews with teachers, school principals, students, and parents, as well as direct observation in the schools. Secondary data were collected from curriculum documents, school annual reports, academic publications, and related literature. Data analysis was carried out using thematic analysis to identify key themes and comparative analysis to compare findings from both countries. The findings reveal that: 1. The integration of religious and cultural values in religious education in both countries plays a significant role in shaping students' character. In Indonesia, local cultural values such as mutual cooperation (gotong royong) and patriotism are integrated with Islamic religious education to create a holistic curriculum. In Malaysia, Malay cultural values are combined with Islamic teachings to impart moral and ethical values. This integration has proven effective in fostering moral and ethical character development among students in both countries. 2. The study also found that for character development, more elaborate approaches are needed, such as developing an integrated curriculum, conducting culture-based extracurricular activities, enhancing teacher competence, and utilizing technology in learning. Furthermore, the study recommends strengthening cooperation between Indonesia and Malaysia in the field of religious education to share experiences and best practices, as well as developing more flexible and contextual education policies in line with societal dynamics and contemporary developments.